Pengaruh Aktiva Tetap, Persediaan, Hutang dan Beban Penjualan terhadap Laba Bersih pada Perusahaan Perdagangan Besar Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019 - Adam Afiezan; Minar Register Sitorus; Juwita Melissa Lumbantobing (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The present study is a quantitative one aimed at determining the effect of fixed asset, inventory, liability and sale cost on net profit of large trading companies. The population includes 62 large trading companies listed on Indonesia Stock Exchange within period of 2016-2019. The sampling method used a purposive sampling method with certain criteria by which there were 15 companies obtained so that there were 60 emittent for 4 years. The data is secondary data obtained from www.idx.co.id. The collected data were then analyzed by using a multiple linear regression analysis. The result of the study shown that fixed assets, inventories, liabilities and selling expenses simultaneously have a significant effect on net income. It is indicated by F-Count (27.256) > F- table (2.38) and sig-p (0,000) < 0,05. Fixed asset partially has a significant effect on net income. Inventory partially has a significant effect on net income. Liability partially does not have a significant effect on net income. Selling expenses partially has a significant effect on net income. It is suggested to the trading companies to pay more attention to aspects that affect good profit so that Net Profits can be further increased. Keywords : Fixed Asset, Inventory, Liability and Sale Cost.